Seasonal variation and meat composition of blue crab (Callinectes sapidus, RATHBUN, 1896) caught in Iskenderun Bay, North-East Mediterranean - (:unkn) unknown (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY, 2002)
The seasonal variation and meat composition of blue crabs (Callinectes sapidus Rathbun, 1896) were investigated. Twenty (10 male, 10 female) crabs were used each season. The total weight of the samples was estimated and the ratios of crude protein, lipid, dry matter and crude ash were obtained from meat of the body and claws. Comparatively higher values of dry matter, crude ash and lipid were determined for the claw meat of males in winter. In the same season the crude protein and lipid composition of claws and crude ash of body meat were higher in females than other meat. The highest ratio of crude protein (21.96%) from female body meat and dry matter (26.15%) from male cheliped meat was in spring. Crude ash (3.28%) was highest for female body meat in winter and lipid (3.89%) was highest for male body meat in spring.
Keywords: Iskenderun Bay; Callinectes sapidus; blue crab; meat composition